ISOLATION OF STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI; THE IMPORTANT FOOD BORNE PATHOGENS FROM SEVERAL RESTAURANTS IN BASRAH CITY, IRAQ. - Nidham Jamalludeen (Basrah Journal of Veterinary Research)
The goal of this research was to isolate, identify and characterize Staphylococcus aureus,Escherichia coli and some other foodborne pathogens from randomly public distributedrestaurants in Basrah city, Iraq. Of the 134 bacterial isolates from restaurants samples, 36 wereconfirmed as S. aureus and out of 141 isolates, 72 were confirmed as E. coli using differentselective and enrichment bacteriological media. Data results of other microorganisms have beenexcluded from this study. However, result from this work indicates that preventive anddisinfectant plans should be considered to ensure contamination free restaurants for the betterhealth of all consumers.